Resiliensi dan Harapan Mendorong Flourishing pada Keluarga Pengasuh Pasien Penyakit Kronis - Angelia Hanna Stevany; IGAA Noviekayati; Amherstia Pasca Rina (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2026)
Individuals with chronic illnesses depend on family caregivers due to the severity of their illness, causing physical, emotional, and economic burdens that increase the risk of depression and fatigue. This has the potential to reduce the quality of care, increase the risk of patient relapse, and cause family dysfunction. This study aims to determine the relationship between resilience and hope with flourishing in family caregivers of individuals with chronic illnesses, both partially and simultaneously. The study used a correlational quantitative approach with purposive sampling techniques. The sample consisted of 85 family caregivers. The measurement tools included the Secure Flourishing Index, Connor-Davidson Resilience Scale, and Herth Hope Index. Data analysis techniques used multiple regression to test the predictors of flourishing in family caregivers of individuals with chronic diseases. The results of the study simultaneously showed a significant relationship between the variables of resilience and hope with flourishing in family caregivers of individuals with chronic diseases. Partially, the variable of resilience with flourishing showed very significant results with a positive direction, and the variable of hope with flourishing showed very significant results with a positive direction. Keywords: Family Caregiver; Flourishing; Hope; Individuals with Chronic Diseases; Resilience Individu dengan penyakit kronis bergantung pada family caregiver akibat keparahan penyakitnya, menyebabkan beban fisik, emosional, dan ekonomi yang meningkatkan risiko depresi serta kelelahan. Hal ini berpotensi menurunkan kualitas perawatan, meningkatkan risiko relaps pasien, dan menyebabkan disfungsi keluarga. Penelitian ini bertujuan untuk mengetahui hubungan resiliensi dan harapan dengan flourishing pada family caregiver individu dengan penyakit kronis, baik secara parsial maupun simultan. Penelitian menggunakan pendekatan kuantitatif korelasional dengan teknik purposive sampling. Sampel berjumlah 85 family caregiver. Alat ukur meliputi the Secure Flourishing Index, Connor-Davidson Resilience Scale, dan Herth Hope Index. Teknik analisis data menggunakan regresi berganda untuk menguji prediktor flourishing pada family caregiver individu dengan penyakit kronis. Hasil penelitian secara simultan menunjukkan adanya hubungan yang signifikan variabel resiliensi dan harapan dengan flourishing pada family caregiver individu dengan penyakit kronis. Secara parsial variabel resiliensi dengan flourishing menunjukkan hasil yang sangat signifikan dengan arah yang positif dan variabel harapan dengan flourishing menunjukkan hasil yang sangat signifikan dengan arah yang positif. Kata kunci: Family Caregiver; Flourishing; Harapan; Individu dengan Penyakit Kronis; Resiliensi